Low-cost electromagnet for extraction of metallic intraocular foreign body - Joselito Joel R. Castro Jr., MD; Rodolfo U. Chuanico, MD, FACS (Philippine Journal of Ophthalmology)
Objective: To develop a low-cost electromagnet for extraction of metallic intraocular foreign body.